IMPLEMENTASI E-GOVERNMENT DALAM PENGELOLAAN KEUANGAN DESA DI KECAMATAN MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - Lambey, Trintje; Lesawengen, Lisbeth; Tulung, Trilke (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The aim of this research is the implementation of E-Government in the management of village finances in the Motoling Timur District, South Minahasa Regency. The development of communication technology has changed the dominant communication paradigm that previously felt one-directional – from the government to the community. The development of communication technology also expands the opportunity for two-way communication, namely between the community and the government and vice versa. This is where the change or transformation occurs in the government's working mechanisms, which are now oriented towards information management and communication strategies. Electronic Government or e-government or e-govt refers to the use of internet networks in disseminating information and providing services from the government to the public. The use of e-government-based applications, especially in villages, has begun to be applied, particularly in the management of village finances, but there are still many issues overshadowing the implementation of such policies. The use of e-government-based applications, especially in villages, has started to be implemented particularly in village financial management. However, there are still many issues overshadowing the implementation of this policy. The research employs a qualitative method through field observation and online data tracking related to the policy of using information technology in government, especially in village financial management. The level of E-Government Implementation: The use of e-government in village financial management in Motoling Timur District shows progress, especially in financial recording, budget transparency, and reporting. However, the level of implementation varies among villages, depending on the readiness of infrastructure and the competence of village officials.